Sistem Monitoring Suhu-Kelembapan Dan Keamanan Rumah Walet Berbasis Internet of Things Menggunakan MQTT - Tri Ananda, Erwin; Usman, Saifudin; Indah Pradasari, Novi (Applied Information Technology and Computer Science (AICOMS), 2023)
Swiftlets are a type of bird with high economic value, especially due to their saliva, which is used as a raw material in health and beauty products. In swiftlet farming, maintaining optimal environmental conditions—specifically a temperature range of 26–29°C and humidity levels of 80–90%—is essential. However, two main challenges faced by swiftlet house owners are the difficulty in monitoring temperature and humidity in real-time and the increasing threat of nest theft. This study aims to develop a temperature, humidity, and security monitoring system for swiftlet houses based on the Internet of Things (IoT) using the MQTT Broker protocol. The system integrates the DHT11 sensor to measure temperature and humidity, an LDR sensor to detect light intensity, and a magnetic switch to monitor door access. The research methodology follows the Software Development Life Cycle (SDLC) using the Waterfall model, with data collection techniques including literature studies, observation, and interviews. The development process involves system architecture design, hardware setup, data flow modeling, interface design, and system testing. The final outcome is an IoT-based monitoring system that provides real-time environmental data and security notifications via Telegram and a visual interface using Node-RED. Black box testing confirms that all sensors and notification systems function correctly as intended